2013 IEEE Frontiers in Education Conference (FIE) 2013
DOI: 10.1109/fie.2013.6685160
|View full text |Cite
|
Sign up to set email alerts
|

Women in computing A case study about Kuwait

Abstract: Female under-representation in the field of computing has been a global concern. A ccording to recent research studies in the US, females are less likely than males to consider a career or a degree in computer-related fields. Opposite trends have been appearing in other parts of the world showing a high female turnout in computer studies. One of those countries is Kuwait, a small country situated in the Persian Gulf. According the UNESCO Institute for Statistics, the percentage of female graduates in tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…On the other hand, Heinze and Hu [30] argue that support from family and friends is not a powerful influence on the choice of students to pursue careers in IT. Social support and role models were not considered top factors for CS students in studies in Kuwait [21], Armenia [24] or Serbia [42].…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Heinze and Hu [30] argue that support from family and friends is not a powerful influence on the choice of students to pursue careers in IT. Social support and role models were not considered top factors for CS students in studies in Kuwait [21], Armenia [24] or Serbia [42].…”
Section: Social Supportmentioning
confidence: 99%
“…Advisers should be aware of negative expectations, because some of these expectations are often misguided, or illogical, and may influence students' choices [54]. In Kuwait, El-Bahey and Zeid [21] found that the most important factor influencing a decision to study CS to be career and future considerations. A Google investigation [25] into factors that influence young women to pursue degrees in CS found that the "…perception of Computer Science as a career with diverse applications and a broad potential for positive societal impact" was a top factor.…”
Section: Outcome Expectationmentioning
confidence: 99%
“…MEAD is a method such as of several stages used to enhance work systems [17]. This method is related to designing, analyzing, and evaluating work systems in organizations so that they become effective and efficient [18] 1.…”
Section: Implementation Of Macro Ergonomic Analysis and Designmentioning
confidence: 99%
“…Service Industry Heidarimoghadam, et al [2], Carayon [4], Carayon, et al [12], El-Bahey & Zeib [17], Suzianti, et al [18], Okta, et al [23], Debastiani, et al [25] Manufacture Realyvásquez, et al [5], Taghipour, et al [6], Pradini, et al [19], Kurniawan, et al [21], Sari,et al [22], Azadeh, et al [24] Office Environment…”
Section: Application Of Macro Ergonomics Publicationmentioning
confidence: 99%
See 1 more Smart Citation